Predicting Factors of Early Postoperative Complications in Extremities Injury Patients - Peerawasthanawut, Nantiphak; Danaidutsadeekul, Suporn; Wongkongkam, Kessiri; Chinaroonchai, Kusuma (Journal of The Royal Thai Army Nurses, 2024)
This research aimed to study the severity of the injury, the period from injury to surgery, body mass index, and the surgical frailty to early postoperative complications in patients with extremity injuries. The sample was patients with extremity injuries and/or injuries of other systems who underwent 146 extremity surgeries. The instruments used for data collection were The Injury Severity Score, The 5-Item Modified Frailty Index, and The Adapted Clavien Dindo in trauma. Statistical analysis using Logistic regression with enter method. The results of the analysis found that the severity of the injury, the period from injury to surgery, and the surgical frailty could predict the early postoperative complications in patients with extremity injuries for 40.5% with statistical significance (Nagelkerke R2 = .405, p< .05). Therefore, this knowledge should be applied to create a guideline for preoperative and postoperative care and prevention of severe complications in patients with extremity injuries. The results of this study are used as information for planning with a multidisciplinary team in caring for patients with extremity injuries who have undergone surgery and preventing possible complications.